Transcriptional analysis of rolling circle replicating plasmid pVT736-1: evidence for replication control by antisense RNA. - Galli, D M (1995)
Several plasmids have been described in Actinobacillus actinomycetemcomitans, a gram-negative coccobacillus. Recently, the nucleotide sequence of pVT736-1, a cryptic plasmid of A. actinomycetemcomitans VT736, was determined. This plasmid possesses all the features necessary for rolling circle replication. The present study involved a transcriptional analysis of pVT736-1. Results of Northern (RNA) blot analyses and primer extension studies indicated that the two open reading frames identified in pVT736-1 are each preceded by at least one promoter. Expression of these promoters varied with growth phase. In addition, an antisense RNA (Cop RNA) appeared to control the synthesis of the putative replication protein. To our knowledge, this is the first rolling circle replicating plasmid isolated from a gram-negative organism that has been subjected to such detailed analysis.